NADPH–Cytochrome P450 Reductase Mediates the Resistance of Aphis (Toxoptera) citricidus (Kirkaldy) to Abamectin - Jing, Tian-Xing; Tan, Yang; Ding, Bi-Yue; Dou, Wei; Wei, Dan-Dan; Wang, Jin-Jun (Frontiers in Physiology, 2018)
NADPH-cytochrome P450 reductase (CPR) plays an essential role in the cytochrome P450 enzyme system, which aids in the metabolism of endogenous and exogenous compounds including the detoxification of insecticides. In this study, the CPR transcript in Aphis (Toxoptera) citricidus (Kirkaldy) was cloned, and the deduced amino-acid sequence contained an N-terminal membrane anchor, three conserved binding domains (flavin mononucleotide, flavin adeninedinucleotide and nicotinamide adenine dinucleotide phosphate), a flavin adeninedinucleotide-binding motif and catalytic residues. The gene was grouped in the hemipteran branch of an insect CPR sequence based on phylogenetic analysis. AcCPR was ubiquitously expressed at all developmental stages, and was most abundant in the adults and least abundant in third-instar nymphs. Compared with other tested tissues of adults, AcCPR was significantly highly expressed in gut. Feeding double-stranded RNA of AcCPR reduced the AcCPR mRNA level in aphids, and the tested insects exhibited higher susceptibility to abamectin than controls. Furthermore, the heterologous overexpression of AcCPR in Sf9 cells resulted in a greater viability than control cells when treated with abamectin. Therefore, AcCPR may contribute to the susceptibility of A. citricidus to abamectin, and CPR may be a potential target for novel insecticide design or a new factor in the development of insecticide resistance.